Artificial intelligence in supporting students’ descriptive writing through PjBL learning model: The pedagogical design and its practice - Ammade, Salasiah; Ramiana; NurRafi’ah (Proceder: Applied Linguistics, Literature, and Language Education, 2025)
Artificial intelligence (AI) tools that support teaching have been widely practiced by teachers in the education world. Yet, the steps to practice it or its teaching design are still limited to previous studies. Therefore, the study focuses on the design and implementation aspects of teaching descriptive writing through project-based learning and integrating artificial intelligence (AI) tools. The research location is at a junior high school in Soppeng, Indonesia, and the research subject was seventh-grade students. The result of the teaching design covers steps, activities, materials, Artificial Intelligence tools, media, and evaluation. The steps and activities in the teaching design consist of opening, main teaching, and closing. In the teaching material part, the contents describe animals, people, and places. In the AI tools part, the tools used in teaching are Gencraft, chat GPT, and Padlet. In the media part, the tools used are LCD, smartphone, and laptop. Students’ writing documents were evaluated using a writing rubric in the evaluation part. The study has identified the steps in designing a teaching model for descriptive writing through Pjbl learning by integrating AI tools. This study contributes to our knowledge of the various procedures in teaching design. Yet, future studies on the current topics are still recommended to enrich the research areas on pedagogical design.